Comparison of cephalometric measurements of living subjects and ancient skulls in Anatolia - Akbulut, Sibel; Nigar Karadeniz, Secil; Sebnem Kursun Cakmak, Emine; Bayrak, Seval; Sahin, Serkan; Orhan, Kaan (Annals of Medical Research, 2021)
Aim: This study aims to provide insights into the evolutionary adaptation of human, via comparing the craniofacial characteristics of living subjects and ancient skulls from Anatolia. Material and Methods: Cone-beam computed tomography (CBCT) generated 2D cephalometric projections of 32 ancient skulls and well matched lateral cephalometric images of 32 patients were evaluated. Sixteen widely used cephalometric measurements were performed. Intra-class correlation coefficients were used to examine intra-observer reliability. Mann–Whitney tests and chi-square tests were used to compare cephalometric measurements of the groups.Results: The linear measurements of living subjects were smaller than the linear measurements of ancient skulls (p0.05). Significant differences were found between the groups in the cranial base lengths, maxillary and mandibular dimensions (p0.05). The maxilla and mandible were found more prognathic in ancient men and women (p0.001).Conclusion: Environmental factors and genetic changes lead to a reduction in the sagittal and vertical dimensions of the human craniofacial complex. Dental practitioners should consider these evolutionary changes during the treatment planning process.
Keywords: Anatolia; ancient populations; craniofacial measurements; cephalograms